Analisis penyajian aset tidak berwujud pada laporan keuangan - Deva Anggraeni Rahmadiah; Denna Taris Citra Rahadiansyah; Shafira Putri Callista; Diza Amalia; Raihan Aqil Fauzananda Musrady (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Intangible assets are non-monetary assets that have a value and useful life of more than one year. The purpose of this study is to determine the application of intangible assets to LQ45 companies listed on the Indonesia Stock Exchange in 2020. The data in this study uses secondary data obtained from LQ45 companies listed on the Indonesia Stock Exchange in 2020 that apply intangible assets to their financial statements. The method of determining the sample using purposive sampling technique in order to obtain 24 of 42 companies that are used as objects of research and qualitative descriptive methods to analyze the presentation of intangible assets in the statement of financial position and notes to financial statements. The results show that the majority of LQ45 companies present intangible assets in the financial statements.